2006
DOI: 10.4046/trd.2006.61.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Application of Noninvasive Positive Pressure Ventilation in Patients with Respiratory Failure

Abstract: Background: Noninvasive positive pressure ventilation(NPPV) has been increasingly used over the past decade in the management of acute or chronic respiratory failure and weaning of mechanical ventilation. We performed this clinical study to evaluate the usefulness of NPPV in patients who developed acute respiratory failure or post-extubation respiratory failure. Methods: We analysed thirty four patients(sixteen males and eighteen females, mean ages 58 years) who applied NPPV(BIPAP S/T, Respironics co., USA) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Various studies on the usefulness of ventilator treatment and non-invasive positive pressure ventilation (NPPV) have shown that the frequency of intubation in the trachea is low, and there is a reduction in the length of hospitalization, readmission rate, and mortality rate [ 9 , 10 , 11 ]. However, for the application and maintenance of NPPV, the time and effort required by skilled medical staff are significant factors [ 7 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on the usefulness of ventilator treatment and non-invasive positive pressure ventilation (NPPV) have shown that the frequency of intubation in the trachea is low, and there is a reduction in the length of hospitalization, readmission rate, and mortality rate [ 9 , 10 , 11 ]. However, for the application and maintenance of NPPV, the time and effort required by skilled medical staff are significant factors [ 7 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the role of NIV in the treatment of acute respiratory failure during AE-COPD is well established, with overwhelming evidence of reducing the need for IMV and improved survival in carefully selected patients [9,10,11,12,13,14]. It is thought that this benefit may be mediated, at least in part, through the prevention of complications related with IMV use, including ventilator-associated pneumonia and barotrauma [15].…”
Section: Introductionmentioning
confidence: 99%
“…NIV is preferentially recommended in AECOPD over invasive mechanical ventilation with intubation 12 13 . Trends in mechanical ventilation among patients with AECOPD have been changed.…”
Section: Updated Management Of Aecopd With Acute Respiratory Failurementioning
confidence: 99%